Manifestations of Characterization in the Novel “Al-Tibr” by Ibrahim al-Koni - Abdelkebir , Souhila; benalia, naima (El Omda in Linguistics and Discourse Analysis, 2022)
. This research aims to highlight the role of the character, as it has an important role because it is the main actor in the novel and through which events develop. It is able to clearly highlight the reality through the symbols and ideas it carries to complete the event, and through which the writer can reach his goal. Therefore, we shed light on this element to discover the extent to which the novelist has succeeded in employing it, besides to entering its world and the evidence it bears within the novel and its effects on other narrative elements. We saw it appropriate to define it, and clarify its importance, specifications, and its relationship with other narrative components, as we referred to the manifestations of the character in the novel Al-Tibr, where we mentioned the main, secondary and marginal characters, accompanied by the analysis, by extracting samples from the novel.